Galleria mellonella for systemic assessment of anti-Candida auris using amphotericin B loaded in nanoemulsion - Marena, Gabriel Davi [UNESP]; Ramos, Matheus Aparecido Dos Santos [UNESP]; Lima, Laura Caminitti [UNESP]; Chorilli, Marlus [UNESP]; Bauab, Tais Maria [UNESP] (Elsevier, 2022)
Galleria mellonella is a model that uses adult larvae to assess the prophylactic, therapeutic, and acute toxic potential of substances. Given their benefits, G. mellonella models are being employed in investigations of systemic infections caused by highly resistant microorganisms. Among the multiresistant microorganisms, we highlight Candida auris, a yeast with high mortality potential and resistance. Among the potential drugs, amphotericin B (AmB) stands out; however, microbial resistance episodes and side effects caused by low selectivity have been observed. The incorporation of AmB into a nanoemulsion (NE) can contribute to the control of C. auris infections and resistance as well as decrease the side effects of this drug. This study aimed to develop AmB-loaded NE (NEA) and evaluate its antifungal action against C. auris in G. mellonella. NEs were obtained by using sunflower oil and cholesterol as the oily phase, polyoxyethylene 20 cetyl ether (Brij® 58) and soy phosphatidylcholine as the surfactant system, and PBS buffer as the aqueous phase. An alternative in vivo assay with G. mellonella for acute toxicity and infection was performed using adult stage larvae (200 mg to 400 mg). According to the obtained results, NE and NEA exhibited sizes of 43 and 48 nm, respectively. The PDI was 0.285 and 0.389 for NE and NEA, respectively. The ZP showed electronegativity for both systems, with −3.77 mV and −3.80 mV for NE and NEA, respectively. Acute toxicity showed that free AmB had greater acute toxicity potential than NEA. The survival assay showed high larval viability. NEA had a better antifungal profile against systemic infection in G. mellonella. It is concluded that the alternative model proved to be an efficient in vivo assay to determine the toxicity and evaluate the therapeutic property of free AmB and NEA in systemic infections caused by C. auris.
Keywords: Amphotericin B; Candida auris; Galleria mellonella; Nanoemulsion; Systemic infection